Bibliometric Analysis of Tourism Marketing in Business Growth - Loso Judijanto (Westscience Press, 2025)
This study examines the intellectual structure, thematic evolution, and global research trends in tourism marketing and its contribution to business growth through a bibliometric approach. Using publications indexed in the Scopus database from 2000 to 2025, the study applies bibliometric and network analysis techniques supported by VOSviewer to map keyword co-occurrence, co-authorship patterns, citation structures, and country-level collaborations. The findings reveal that tourism marketing research is strongly anchored in themes such as digital marketing, customer satisfaction, sustainability, and business performance, reflecting the sector’s transformation in response to technological advancement and changing consumer behavior. Emerging topics, including social media marketing, artificial intelligence, and sustainable tourism practices, indicate a growing shift toward data-driven and experience-oriented marketing strategies. The analysis also highlights the dominance of collaborative research networks involving developed and emerging economies, underscoring the global nature of tourism marketing knowledge production. By synthesizing fragmented literature into a coherent knowledge map, this study contributes theoretically by clarifying the evolution and convergence of tourism marketing themes, and practically by providing insights for tourism businesses and policymakers to design evidence-based marketing strategies that support sustainable business growth.